A description of the Yunnan English accent. Issue 1 (26th October 2015) - AO, RAN; LOW, EE LING
ABSTRACT: This paper presents findings of an acoustic investigation of monophthong vowels produced by learners of English from Yunnan, China. Speech data for the present study were collected from 15 participants comprising five Han Chinese English majors, five Han Chinese non‐English majors and five Yi minority ethnic English majors. The findings show that the three groups share more differences than similarities in terms of vowel duration but not in terms of vowel quality though the results of Euclidean distance show that the Han Chinese English majors and the Han Chinese non‐English majors are different from the Yi minority ethnic English majors. Results of standard deviation reveal that the Yi minority ethnic English majors have the lowest inter‐speaker variability, followed by the Han Chinese English majors and the Han Chinese non‐English majors.